Differential transcriptional control of hematopoiesis in congenital and cyclic neutropenia patients harboring ELANE mutations - Zeidler, Alexander; Borbaran-Bravo, Natalia; Dannenmann, Benjamin; Ritter, Malte; Nasri, Masoud; Klimiankou, Maksim; Kandabarau, Sergey; Zahabi, Azadeh; König, Josef; Zeidler, Cornelia; Skokowa, Julia; Welte, Karl (Haematologica, 2024)
Mutations in the ELANE gene, encoding the neutrophil elastase (NE) protein, are responsible for most cyclic neutropenia (CyN) cases and approximately 25% of congenital neutropenia (CN) cases. In CN and in CyN, a median of 2.8% of CD34+ cells were early CD49f+ hematopoietic stem cells (eHSC) that did not express ELANE and thus escape from the unfolded protein response (UPR) caused by mutated NE. In CyN, the CD49f+ cells respond to granulocyte colony-stimulating factor (G-CSF) with a significant upregulation of the hematopoietic stem cell-specific transcription factors, C/EBPα, MLL1, HOXA9, MEIS1, and HLF during the ascending arm of the cycle, resulting in the differentiation of myeloid cells to mature neutrophils at the cycle peak. However, NE protein released by neutrophils at the cycle’s peak caused a negative feedback loop on granulopoiesis through the proteolytic digestion of G-CSF. In contrast, in CN patients, CD49f+ cells failed to express mRNA levels of HSC-specific transcription factors mentioned above. Rescue of C/EBPα expression in CN restored granulopoiesis.